De Novo Analysis of Wolfiporia cocos Transcriptome to Reveal the Differentially Expressed Carbohydrate-Active Enzymes (CAZymes) Genes During the Early Stage of Sclerotial Growth - Zhang, Shaopeng; Hu, Bingxiong; Wei, Wei; Xiong, Ying; Zhu, Wenjun; Peng, Fang; Yu, Yang; Zheng, Yonglian; Chen, Ping (Frontiers in Microbiology, 2016)
The sclerotium of Wolfiporia cocos has been used as an edible mushroom and/or a traditional herbal medicine for centuries. W. cocos sclerotial formation is dependent on parasitism of the wood of Pinus species. Currently, the sclerotial development mechanisms of W. cocos remain largely unknown and the lack of pine resources limit the commercial production. The CAZymes (carbohydrate-active enzymes) play important roles in degradation of the plant cell wall to provide carbohydrates for fungal growth, development and reproduction. In this study, the transcript profiles from W. cocos mycelium and two-months-old sclerotium, the early stage of sclerotial growth, were specially analyzed using de novo sequencing technology. A total of 142,428,180 high-quality reads of mycelium and 70,594,319 high-quality reads of two-months-old sclerotium were obtained. Additionally, differentially expressed genes from the W. cocos mycelium and two-months-old sclerotium stages were analyzed, resulting in identification of 69 CAZymes genes which were significantly up-regulated during the early stage of sclerotial growth compared to that of in mycelium stage, and more than half of them belonged to glycosyl hydrolases (GHs) family, indicating the importance of W. cocos GHs family for degrading the pine woods. And qRT-PCR was further used to confirm the expression pattern of these up-regulated CAZymes genes. Our results will provide comprehensive CAZymes genes expression information during W. cocos sclerotial growth at the transcriptional level and will lay a foundation for functional genes studies in this fungus. In addition, our study will also facilitate the efficient use of limited pine resources, which is significant for promoting steady development of Chinese W. cocos industry.